A case report of detecting subclinical coagulopathy in a patient with boomslang (Dipholidus typus) bite - Mungela J. Tambwe; Vidya Lalloo; Andreas Engelbrecht; Pholosho Pelle (South African Family Practice)
The boomslang (Dipholidus typus) has a predominantly haemotoxic venom. Because of the consumptive nature of the coagulopathy, signs and symptoms are usually delayed by up to 72 h after the bite. Traditional laboratory coagulation assays have a long turnaround time, by which time the patient’s bleeding and clotting profile has changed. A 25-year-old male patient was bitten by a boomslang. Despite two normal laboratory coagulation assay results, a point-of-care rotational thromboelastometry showed low fibrinogen levels, leading to the administration of monovalent antivenom. This report highlights the value of point-of-care thromboelastometry in the care of patients with subclinical boomslang envenomation.